Destiny disrupted : a history of the world through Islamic eyes - Ansary, Mir Tamim (PublicAffairs, 2009)
"We in the West share a common narrative of world history: It runs from ancient Egypt and Mesopotamia, through Greece and Rome, through the rise of Christianity and the Dark Ages, through the Renaissance, the Reformation, and the Enlightenment, to industrialism, the secular state, and the triumph of democracy. As a young history buff growing up in Muslim Afghanistan, Tamim Ansary absorbed this narrative but also knew that it sidelined an entire civilization, one that had seen itself at the center of the global narrative for over a thousand years."